Noise Pollution in Healthcare Settings: Impacts on Patient Recovery and Staff Well-Being - Amit Shishodia (International Journal of Environmental Noise and Pollution Control, 2023)
Healthcare environments frequently experience noise pollution, which has serious effects on both patient recovery and the well-being of healthcare staff. This extensive research study includes patient rooms, waiting spaces, and corridors as part of its effort to measure and categorize noise levels. The study explores the complex effects of noise pollution on patients and healthcare personnel by integrating quantitative measures, surveys, and qualitative evaluations. According to preliminary research, loud surroundings in healthcare institutions are bad for patients' sleep, satisfaction, and ultimately, their ability to recover. Additionally, workers in the healthcare industry who are exposed to high noise levels show worsened stress symptoms and lower job satisfaction. This study's findings about the sources of noise pollution cover a wide range, including alarms, machinery, intercom systems, and building infrastructure. The findings of this study highlight how urgent it is to eliminate noise pollution in hospital settings. The introduction of noise-reducing technologies, personnel training, and soundproofing methods are among the proposed mitigation options. These discoveries could revolutionize the way healthcare is delivered by creating an atmosphere that is more supportive of staff morale and patient wellbeing, which would eventually improve the standard of care. This study marks a significant step forward in the creation of evidence-based interventions and policy recommendations designed to reduce noise pollution in hospital settings and improve the quality of care for all parties concerned.
Keywords: Ambient noise levels; Healthcare settings; Noise pollution; Patient recovery; Staff well-being